If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x = 8 + 7x Solving 6x = 8 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 6x + -7x = 8 + 7x + -7x Combine like terms: 6x + -7x = -1x -1x = 8 + 7x + -7x Combine like terms: 7x + -7x = 0 -1x = 8 + 0 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8
| 20=4(x+7) | | 4y+8=16 | | 3x-2x+8-10=7 | | 10+x=28 | | -4x-4+x-2y+7x= | | 2=3(x+7)+2 | | 4-(7n-5)+18n=5(5n+1) | | 25=-3k+5(k+7) | | 2x+3=19+5x | | x^2-0.3=-0.06x | | 9(2a-3)-5(3a-2)=-a+9(a-8) | | 5d-17-3d+18=15d+17-11d | | -8-4(2q-3)=-16 | | 7=-5(5+7n)-3 | | 7n-1=3k-5 | | -8(1+8a)=-8 | | 4x^2+18x+20=0 | | -(-7+1)=-(-3-8q) | | 8*(2x+1)-(11-2)*x=6 | | x-7y=-14 | | 0=14t^2+16t+1798 | | 6[x-2(2x+3)+1]+3(5+6x)+x=0 | | 1.76=a-2.84 | | x+x-2+x+1=62 | | 8x^2-4x-60=0 | | 6x-14=6x+6-3x | | 10+2x=328 | | 6x-14=8x+8-3x | | 6x-14=5x+5-3x | | 7x-2=-3x | | 2w^2-3w-90=0 | | 5n-2=3n+6 |